2004
DOI: 10.1074/jbc.m407176200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tyrosine Phosphorylation in the Regulation of Cleavage Secretion of Angiotensin-converting Enzyme

Abstract: Both germinal (gACE) and somatic (sACE) isozymes of angiotensin-converting enzyme (ACE) are type I ectoproteins whose enzymatically active ectodomains are cleaved and shed by a membrane-bound protease. Here, we report a role of protein tyrosine phosphorylation in regulating this process. Strong enhancements of ACE cleavage secretion was observed upon enhancing protein Tyr phosphorylation by treating gACE-or sACEexpressing cells with pervanadate, an inhibitor of protein Tyr phosphatases. Secreted gACE, cell-bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The concentration of AII in the culture media was not increased under the pressurized condition in our experiments, which may due to the absence of angiotensin I (data not shown). Although other mechanisms may be involved [29,30], our findings in this study suggest that the expression and activity of ACE in HASMCs were partly controlled by local AII produced by the ACE in HASMCs themselves, indicating the existence of a local negative feedback effect in addition to the systemic feedback produced by circulating AII.…”
Section: N Nmentioning
confidence: 63%
“…The concentration of AII in the culture media was not increased under the pressurized condition in our experiments, which may due to the absence of angiotensin I (data not shown). Although other mechanisms may be involved [29,30], our findings in this study suggest that the expression and activity of ACE in HASMCs were partly controlled by local AII produced by the ACE in HASMCs themselves, indicating the existence of a local negative feedback effect in addition to the systemic feedback produced by circulating AII.…”
Section: N Nmentioning
confidence: 63%
“…Recently we also showed that tyrosine phosphorylation of the ectodomain of ACE regulates ACE shedding (28). Here we show that ACE is also phosphorylated on a specific serine residue of the cytoplasmic domain.…”
mentioning
confidence: 65%
“…Therefore, the regulation of ACE cleavage secretion might be necessary for maintaining this balance. Our previous studies have demonstrated that ACE shedding is a regulated process, which could be stimulated by PMA, an activator of protein kinase C (24), or pervanadate, an inhibitor of tyrosine phosphatases (28), and inhibited by inhibitors of specific class of metalloproteases (22). Specific cellular proteins are associated with ACE molecules and regulate the ACE shedding process (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some differences in the cytoplasmic domains of the two proteins; for example, the cleavage/secretion of rabbit testicular ACE has been reported to be regulated by the tyrosine phosphorylation of its cytoplasmic tail (Santhamma et al, 2004), whereas the cytoplasmic domain of human somatic ACE does not contain a tyrosine residue. We were also unable to detect a direct effect of PKC on the phosphorylation of ACE-associated MYH9.…”
Section: Myh9 Phosphorylation By Ace Signaling 23mentioning
confidence: 99%